Murcha de fusário em cafeeiro conilon: patogenicidade, metodologias de inoculação e diagnose molecular - Ferreira, Mila Letice Sangali Mattos (2021)
Brazil stands out as the largest producer and exporter of coffees in the world. However, the occurrence of diseases is a limiting factor for increasing production and productivity, affecting socially and economically coffee farmers. In conilon coffee (Coffea canephora), fusarium wilt is caused by fungi of the Fusarium spp. complex, which can affect coffee plants, causing, among other symptoms, wilting, defoliation and darkening of the vascular tissue, culminating in yield losses and the quality of the culture. In view of this scenario, Fusarium spp. in conilon coffee, verifying its efficiency for studies and making it possible to accelerate the diagnosis and development of resistance tests. The work was conducted using three methodologies, the first involving conidial inoculation in leaf discs (ICF), conducted in the laboratory. Four isolates of Fusarium spp. were tested in 2 coffee clones (LB1 and CV02) and 2 types of leaf (tender and expanded). The experimental design was completely randomized (DIC), in a triple factorial arrangement with 4 repetitions plus the control. The second and third methodology was carried out in a greenhouse with seedling inoculation . Four Fusarium spp. in 2 coffee clones (LB1 and CV02), and two forms of inoculation (mycelial inoculation in stem cells with injury-BMI and conidial inoculation by root immersion-ICR). The experiment was conducted in DIC, in a triple factorial arrangement with 4 replications, plus two witnesses (a general witness for each clone, where the plants had their roots washed and were transplanted into plastic bags with substrate and as witnesses who received inoculation for each mentioned methodology). In the ICF methodology, three of the four candidates for Fusarium spp. used caused symptoms of the disease, with greater incidence in the discs of expanded leaves. There was no difference between the two clones regarding the intensity of the disease. In the BMI methodology, 90% and 85% of the seedlings of clones LB1 and CV02, respectively, inoculated with isolate 09 (Fusarium solani), removed from the disease from the eighth and tenth days after inoculation (DAI) and produced signs of the disease 13 DAI. In the ICR methodology, 180 DAI there were no symptoms and/or signs of the disease. The ICF methodology is recommended to diagnose the disease, as well as a IMC using Fusarium solani.